ORIENTALISME DAN KEUTUHAN UMMAH ISLAM: SUATU ANALISIS - Abd Rahim, Rahimin Affandi (Jurnal Syariah, 2019)
The article is an attempt to study the significance and effect of the orientalists' work pertaining to the subject of Islamic law. It will be divided into two different sections. First, the significance and positive values of the orientalist's work in the Muslim academia world. Second, the negative methodology utilised by the western orienta lists and its impact upon the Muslim's understanding of Islamic law.